(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This thesis investigates the development, application, and distinctive characteristics of linguistic drawing methodology across China and selected Asian countries (Japan, South Korea, India, Thailand, and Uzbekistan). While linguistic visualization is grounded in widely shared theoretical traditions, the study argues that Asian research communities have developed localized diagramming practices shaped by regional linguistic structures, script traditions, historical trajectories, and research priorities. The thesis pursues four aims: (1) to trace the historical emergence of drawing practices in Asian linguistics from script-based schematic traditions to modern empirical visualizations; (2) to compare core frameworks—syntactic tree diagrams, phonological charts, semantic maps, and sociolinguistic visualizations—across national research contexts